Treatment and outcome of metastatic parathyroid carcinoma: A systematic review and pooled analysis of published cases - Alberti, Andrea; Smussi, Davide; Zamparini, Manuel; Turla, Antonella; Laini, Lara; Marchiselli, Chiara; Grisanti, Salvatore; Bossi, Paolo; Berruti, Alfredo (Frontiers in Oncology, 2022)
Background Parathyroid carcinoma (PC) is an extremely rare malignant tumour with an incidence of about 6 new cases per 10 million population per year. While several papers have been published on treatments and outcomes of PC patients with local-regional disease, little is known about the prognosis and prognostic factors of patients with distant metastasis. Materials and method We performed a pooled analysis and a systematic review of histopathological confirmed PC cases published in literature using the following keywords: ’metastasis – metastatic – secondary nodes’ AND ‘parathyroid carcinoma’. Original case reports and case series reporting metastatic parathyroid carcinoma were included. Data from 59 papers were extracted in a piloted form by five reviewers on a shared database. Results Seventy-seven patients with metastatic PC were identified between 1898 and 2017. Ten (13%) patients had synchronous metastases, metachronous metastases occurred in 41 (53%) patients at first relapse. The remaining 26 patients developed metastatic disease concomitantly to local recurrence. Primary hyperparathyroidism lead the diagnosis of metastatic recurrence in 56 (72%) patients. Surgery was the main primary approach adopted, since it was performed in 43 (56%) patients. Eighteen (23%) patients underwent a systemic antineoplastic therapy, consisting in chemotherapy, immunotherapy, tyrosine kinase inhibitors and hexestrol therapy. Bone resorption inhibitors had a limited efficacy in the long term control of hypercalcemia. After a median follow-up of 37,5 months, 42 (55%) patients died, 21 (50%) due to consequences of uncontrolled PHPT. Median overall survival was 36 months (range 1-252). Surgery was associated to better OS (HR 0.49, IC 95% 0.27-0.91), while bone metastases were a negative prognostic factor (HR 2.6, IC 95% 1.3-5.1). Conclusion Metastatic PC has a relative poor prognosis. The main goals of treatment are to counteract tumor growth and control hypercalcemia. Metastasis surgery is the best approach to achieve a rapid control of PHPT and a longer survival. Target therapies and immunotherapy deserve to be extensively tested in metastatic PCs and strategies to better control hypercalcemia need to be implemented.